Heel pain in young athletes - not always Sever's Disease : A Narrative Review - Jokela, Aleksi; Aho, Joni; Kosola, Jussi; Stenroos, Antti; Sinikumpu, Juha-Jaakko; Maffulli, Nicola; Lempainen, Lasse (Elsevier, 2025)
Heel pain is a prevalent issue in young athletes, often arising from overuse and increased sporting demands. While Sever's Disease is the predominant cause, various other entities, including stress-related injuries and pathologies like tumors and bone lesions, contribute to this condition. The complex hind foot anatomy, encompassing ossicles, physis, and soft tissues, may lead to heel pain. This study aims to provide physicians with a clinically oriented narrative review of adolescent heel pain, supported by illustrative cases.
Conclusion This study aims to offer physicians a comprehensive understanding of the concepts surrounding heel pain in adolescents. By presenting clinically relevant information and illustrated cases, it seeks to enhance medical practitioners' ability to diagnose and manage heel pain effectively in this specific demographic